2014
DOI: 10.1212/wnl.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

The expanding clinical and genetic spectrum of ATP1A3-related disorders

Abstract: AHC and RDP constitute clinical prototypes in a continuous phenotypic spectrum of ATP1A3-related disorders. Intermediate phenotypes combining criteria of both conditions are increasingly recognized. Efficient stepwise mutation analysis of the ATP1A3 gene may prioritize those exons where current state of knowledge indicates mutational clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 28 publications
3
99
0
Order By: Relevance
“…49 In AHC and RDP, the mechanisms contributing to the sudden and often stepwise deterioration seen in both disorders remains poorly understood. In AHC, multifaceted neurological symptoms and signs fluctuate more dramatically, and with a wider range of symptoms and signs than in those with RDP, yet shared features of the additional neurological comorbidities, including cognitive impairment, mood and behavioral disorders, dystonia, and bulbar involvement (especially dysarthria), are compelling.…”
Section: Discussionmentioning
confidence: 99%
“…49 In AHC and RDP, the mechanisms contributing to the sudden and often stepwise deterioration seen in both disorders remains poorly understood. In AHC, multifaceted neurological symptoms and signs fluctuate more dramatically, and with a wider range of symptoms and signs than in those with RDP, yet shared features of the additional neurological comorbidities, including cognitive impairment, mood and behavioral disorders, dystonia, and bulbar involvement (especially dysarthria), are compelling.…”
Section: Discussionmentioning
confidence: 99%
“…The α-3 gene is neuron specific and primarily expressed in central nervous system neurons, notably in GABAergic projection neurons of the basal ganglia (Hieber et al 1991; Lingrel 1992; Bøttger et al 2011). Mutations in this subunit of the protein complex have been documented in association with a spectrum of psychological, psychomotor, and neuromuscular abnormalities (Brashear et al 2007; Ozelius 2012; Rosewich et al 2014; Sweney et al 2015). Therefore, it is valuable to review the documented breadth of phenotypic variation associated with mutations found in this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Typical onset is during adolescence or adulthood in response to a physiological stressor (Barbano et al 2012; Rosewich et al 2014). A variety of triggers have been reported to produce symptom onset, including acute alcohol consumption (Rosewich et al 2012), extreme temperature change, head trauma, fever, strenuous exercise, and psychological stressors (Goldstein et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additional genetic testing revealed a novel heterozygous ATP1A3 genetic mutation, a condition associated with rapid onset dystonia-parkinsonism and alternating hemiplegia of childhood, which can be associated with seizures. [8][9][10][11][12] …”
Section: Case Reportmentioning
confidence: 99%